2011
DOI: 10.1148/rg.314105065
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Appendicitis: Common and Uncommon Gastrointestinal Causes of Right Lower Quadrant Abdominal Pain at Multidetector CT

Abstract: Right lower quadrant abdominal pain is one of the most common causes of a patient visit to the emergency department. Although appendicitis is the most common condition requiring surgery in patients with abdominal pain, right lower quadrant pain can be indicative of a vast list of differential diagnoses and is thus a challenge for clinicians. Other causes of right lower quadrant pain beyond appendicitis include inflammatory and infectious conditions involving the ileocecal region; diverticulitis; malignancies; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 64 publications
0
41
0
2
Order By: Relevance
“…After a positive diagnosis is made using CT, it is standard procedure for the patient to get a follow up colonoscopy around 6 weeks after being diagnosed [9,95]. This is a preventative measure to ensure that the diagnosis of diverticulitis did not miss a diagnosis of colon cancer [77,82,87,91,[95][96][97]. In a study conducted by Lau et al, 34% of patients' follow up colonoscopies came back positive for further complications or misdiagnosis of the initial diverticulitis [97].…”
Section: Endoscopymentioning
confidence: 99%
See 1 more Smart Citation
“…After a positive diagnosis is made using CT, it is standard procedure for the patient to get a follow up colonoscopy around 6 weeks after being diagnosed [9,95]. This is a preventative measure to ensure that the diagnosis of diverticulitis did not miss a diagnosis of colon cancer [77,82,87,91,[95][96][97]. In a study conducted by Lau et al, 34% of patients' follow up colonoscopies came back positive for further complications or misdiagnosis of the initial diverticulitis [97].…”
Section: Endoscopymentioning
confidence: 99%
“…This is a preventative measure to ensure that the diagnosis of diverticulitis did not miss a diagnosis of colon cancer [77,82,87,91,[95][96][97]. In a study conducted by Lau et al, 34% of patients' follow up colonoscopies came back positive for further complications or misdiagnosis of the initial diverticulitis [97]. While there is nothing to indicate that a positive diagnosis for diverticulitis is correlated with a higher risk for colorectal cancer, it has been observed that patients who present with diverticular complications have been more likely to have a positive colonoscopy for colorectal cancer sometime after the diverticulitis diagnosis [77,97].…”
Section: Endoscopymentioning
confidence: 99%
“…6 Because they are larger and more numerous on the left, the most common site of epiploic appendagitis is in the left lower quadrant. 7 Less frequently, the right colon is affected, and the condition mimics acute appendicitis. 6 The function of the appendages is not exactly known but is proposed to be similar to the greater omentum as a form of protection; they also may act as cushioning during peristalsis.…”
Section: Question: What Is Epiploic Appendagitis and Its Pathophysiolmentioning
confidence: 99%
“…Chronic right lower quadrant pain is a clinical presentation for a spectrum of neoplastic and inflammatory diseases that may affect the ileocecal region (1,2). A variety of structures may be pathologically involved, including the cecum, appendix, ileocecal valve and/or terminal ileum; thus, clinically differentiating the source of right lower quadrant pain is challenging (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%